Overproduction of Tk-Subtilisin and Elucidation of Its Structural Thermostability Based on Molecular Dynamics Studies - Nouman Rasool; Naeem Rashid (Brazilian Archives of Biology and Technology)
Abstract Background: Subtilisin from Thermococcus kodakaraensis (Tk-subtilisin) is an ideal candidate for many industrial and research processes due to its unique features. Methods: In this study, the enzyme is overproduced in E. coli using four different media i.e. YNG, M9NG, TB and LB and its thermostability is studies. The production of enzyme is enhanced 10 folds as compared to previously reported data. The role of calcium ions in the thermostability at binding sites 1, 6 and 7, is also analyzed by performing the molecular dynamics simulations at 360K, 375K, 380K and 390K. Results: The enzyme retained its activity when exposed to various protein denaturing agents. The enzyme remained catalytically active in the presence of methanol, 2-propanol, ethyl acetate, toluene and xylene. Tk-subtilisin showed slight collagenase-like activity while did not show any keratinase-like activity. Molecular dynamics simulations revealed RMSD scores were higher for complexes lacking Ca1 i.e. 1.31 to 2.23 and 1.08 to 2.19, for native Tk-subtilisin and its active site mutant, respectively. Conclusions: Thus, Ca1, Ca6 and Ca7 play a fundamental role in the thermostability of enzyme. Specifically, Ca1 is the most vital for thermostability as complexes lacking this calcium ion exhibited less thermostability and incompactness in structure.